Gravity and duality between coordinates and matter fields - Vancea, IV (Elsevier B.V., 2000)
We use the duality between the local Cartezian coordinates and the solutions of the Klein-Gordon equation to parametrize locally the spacetime in terms of wave functions and prepotentials. The components of metric, metric connection, curvature as well as the Einstein equation are given in this parametrization. We also discuss the local duality between coordinates and quantum fields and the metric in this later reparametrization. (C) 2000 Elsevier B.V. B.V. All rights reserved.